Retail Payments : A Practical Guide for Measuring Retail Payment Costs - World Bank Group (World Bank, Washington, DC, 2017)
Retail payment systems play an important role in the smooth functioning of an economy and inefficiencies in the retail payments market can have cascading effects throughout the economy. While there are a number of issues that are responsible for the persistence of inefficiencies in retail payment markets, the lack of a coherent, holistic strategy for the development of retail payment systems is among the most common. In order to develop such a strategy, it is important to economically substantiate the migration from less cost-efficient retail payment instruments (typically cash and paper-based instruments) to more cost-efficient ones (typically electronic payments). Overall, establishing a sound economic baseline for national retail payment systems in terms of costs of different payment instruments can better guide system development and enable high-impact changes. This document is designed to serve as a practical guide for central banks and other public or private-sector stakeholders interested in conducting a study on the costs of day-to-day retail payments in their economies. The results of a cost study based on this methodology can help decision makers to agree on the targeted gains in efficiency in their retail payments system, define an implementation plan for achieving a desired future mix of payment instruments, and provide information for all stakeholders involved in the retail payments market.